How to raise an adult : break free of the overparenting trap and prepare your kid for success - Lythcott-Haims, Julie (Henry Holt and Co., 2015)
" In How to Raise an Adult, Lythcott-Haims draws on research, conversations with educators and employers, and her own insights as a mother and student dean to highlight the ways in which over-parenting harms children and their stressed-out parents. She identifies types of helicopter parents and, while empathizing with parents' universal worries, offers practical alternative strategies that underline the importance of allowing children to make their own mistakes and develop the resilience, resourcefulness, and inner determination necessary for success. Relevant to parents of toddlers as well as of twentysomethings, this book is a rallying cry for those who wish to ensure that the next generation can take charge of their own lives with competence and confidence"--